How do licensed psychotherapists in Germany feel about treating patients with posttraumatic stress symptoms? – an experimental study based on case vignettes. Issue 1 (1st January 2021) - Gossmann, Katharina; Eilers, Rebekka; Rosner, Rita; Barke, Antonia
ABSTRACT: Background: Previous research indicates that not all children, adolescents and adults suffering from PTSD receive psychotherapy and if they do, trauma is not always considered during therapy. One reason for this undertreatment might be a limited readiness of licenced psychotherapists (LPTs) to treat patients who have experienced a trauma and thus suffer from PTSD symptoms. Objective: The aim of this study is to explore the association between the readiness of LPTs to treat patients with PTSD symptoms and different patients' and therapists' characteristics. Method: We used case vignettes to assess the readiness of LPTs in Germany in a nationwide online survey ( N = 768). The vignettes described patients with PTSD and were adapted to the age group mainly treated by the therapists (children/adolescents vs. adults). The patients' characteristics in the otherwise identical vignettes were randomized for patient gender (female vs. male) and symptom cluster (internalizing vs. externalizing). Rating scales were used to assess readiness. Additionally, therapists' characteristics (age, trauma-specific training, perceived fears/doubts, and objective barriers to treating the vignette patient) were assessed. Results: The patients' characteristics did not influence the treatment readiness of the LPTs. Regarding therapists' characteristics, LPTs working mainly with children and adolescents, and those who had completed trauma-specific training reported a higher readiness to treat the vignette patient. Conclusions: Regarding the treatment of patients suffering from PTSD symptoms of different ages, our study indicated that the assessed therapists' characteristics were more relevant for the treatment readiness of LPTs than the patients' characteristics of age or symptom type. HIGHLIGHTS: In this nationwide study based on randomly presented case vignettes, therapists' characteristics like trauma-specific training or fears/doubt were more relevant for the readiness of licenced psychotherapists to treat patients with PTSD symptoms than patients' characteristics.